THE INFLUENCE OF WORK EXPERIENCE AND JOB TRAINING ON PERFORMANCE ON EMPLOYEES AT PT CITRA KARYA JABAR TOL SUMEDANG REGENCY, WEST JAVA - Astri Halawati; Yudiyanto Joko Purnomo (Transpublika Publisher, 2022)
This study aims to identify and measure the performance of PT Citra Karya Jabar Tol Sumedang Regency, West Java. This research uses descriptive research methods with a quantitative approach. The results of the descriptive analysis resulted that the work experience variable consisted of 6 statements with an average score of 127.83 which showed well seen from the assessment table. The results of a descriptive analysis that the job training variable consists of 6 statements with a score of 126.1667 indicates good judging from the scoring table. Furthermore, the performance variable consists of 12 statements with a score of 140.33 indicates good judging from the scoring table. Meanwhile, the work experience regression coefficient of 2,006, means that if the work experience is increased by 1 work unit, the performance will increase by 2,006 units. Likewise, the training regression coefficient of 0.803, means that if the training is increased by 1 unit, the performance will increase by 0.803 units. In addition, R square value of 0.951 or 95.1% was obtained, which means the influence of work experience and training on employee performance in PT. Citra Karya Jabar Tol in West Java simultaneously amounted to 95.1%, while the remaining 4.9% was influenced by other variables beyond this study.